Debate Technique as Teacher's Strategies in Improving Student’s Higher Education English Speaking Skill - Firnantia Lara Lestari (EDUCAFL : Journal of Education of English as Foreign Language, 2018)
Speaking is not only used in public forum but also anytime and anywhere. Speaking also required proficiency in order to make communication clearly. The biggest fear of a student is when they have to speak in public, therefore the lecturer’s willingness to develop the speaking skill for students become very important, it accompanied by strategies that can make students become more courageous to speak in public. To improve the student’s proficiency, teacher needs different strategies based on the skill's differences, such as speaking skill, reading skill and writing skill. Thereby, the different skills required different strategies in order to achieve the different goals and the expected results. This article uses descriptive qualitative as the method in collecting the data. Descriptive qualitative method is used to make a systematic, factual and accurate description, description, or painting of the facts, properties and relationships among the phenomena investigated in terms of words instead of statistics. The result reveals that the excellent score obtained by the students in the vocabulary. The lowest score obtained by the students is in the content of the structure which is the hardest problem that often faced by the higher education students. Moreover, the utilization of this debate technique is effective in order to improve the higher student English speaking skill